Proposed Marketing Strategy for Commercial Medium & Light Turboprop Aircraft in Indonesia (Case Study: PT. Dirgantara Indonesia) - Agnes Grace Florence; Atik Aprianingsih; Heber Mey Fredryk Panjaitan; Dina Rachma Febrina; Bayu Aji Prakoso (IPTEK Journal of Proceedings Series, 2020)
National defense is all efforts to maintain the national sovereignty, the territorial integrity of a state and the safety of all nations from threats and disruption to the integrity of the state. It is important because the strength of the country lies in its defense, which will affect national development. As a national defense industry, PT. Dirgantara Indonesia (PT DI) is responsible for providing defense equipment for its users; Ministry of Defense and the Indonesian National Armed Forces. The product sales contribute 61,79% to the total sales revenue for company. However, this percentage is still far as the targeted then PT DI needs another strategies in order to maintain its business. Since the last 5 years, PT DI only focused on military products. On the other hand, PT DI cannot depend only on sales from military product because there is still high possibility contract cancellation due to changes the policy, the products do not meet as the requirements, or lack of budget. The main problem faced by PT DI is decreasing percentage of aircraft sales. Therefore PT DI needs expanding their market by producing N219 and N245 aircraft for commercial configuration as one of the company's development methods. However to produce new products, PT DI will face main problem that is how PT DI enters the commercial market to increase sales of N219 and N245. The analysis using both internal and external analysis. The company's internal analysis consists of STP analysis and Marketing Mix. Moreover for external analysis, the authors using PESTEL analysis, Porter's 5 forces analysis, competitor analysis, and customer analysis. It is found different perspectives between current marketing mix of PT DI with customer perspectives related to N219 and N245 aircrafts. The existing marketing mix is not optimal and effective. The new propose marketing strategy which consist of product, price, place, and promotion are need to overcome this issue